Influence of Combination Between Fertilizer Treatments and Nipping on Growth, Yield and Quality of Sesame (Sesamum indicum L.) - Sameerah Abubakr Muhammadamin; Bahar Jalal Mahmood (Zanco Journal of Pure and Applied Sciences, 2023)
A field experiment was undertaken during the summer growing season of 2021 at two locations (Grdmala and Grdarasha) - Erbil Governorate to study the influence of five fertilizer types [Control, recommended fertilizer (NPK), Nano-NPK, Humic acid and Nano-NPK+ Humic acid] and two Nipping practice [Without Nipping and with Nipping] on some growth, yield and quality parameters of sesame crop (Somar genotype), using factorial RCBD with three replicates. The results indicated to significant effect of the studied factors and their interactions on the studied characteristics. The maximum seed yield (3.23 and 2.45) t ha-1 was recorded from sprayed with Nano-NPK+ Humic acid and Nano-NPK, while the lowest values (2.41 and 1.43) t ha-1 was recorded from control in both locations respectively. While the highest seed yield value (3.09 and 2.13) t ha-1 were obtained from Nipping practice. On the other hand, the interaction treatment of (Nano-NPK+ Humic acid * Nipping) and (Nano-NPK * Nipping) were recorded the highest seed yield per plant which were (3.77 and 2.61) t ha-1 respectively. The highest oil values (57.71 and 59.49) % was observed from Nano-NPK+ Humic acid and treatment combination of (Nano-NPK+ Humic acid* Nipping) respectively. Furthermore, the results shows that Grdmala surprised Grdarasha in most of the studied parameters.